FACTORS INFLUENCING UNDERGRADUATE ENROLLMENT DECISIONS AMONG FIRST-YEAR STUDENTS AT THE UNIVERSITY OF PHAYAO - Thephinlap, Chonthida; Nontamand, Narinthan; Khrutpan, Wilailak; Promsen , Chonsicha; Intha, Sumittra (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2026)
This study aimed to 1) examine the factors influencing the decision to enroll in undergraduate programs among first-year students at the University of Phayao, and 2) explore their needs for institutional support. A quantitative research design was employed. The participants included 2,346 first-year undergraduate students enrolled in the first semester of the 2025 academic year. Data were collected using a questionnaire assessing factors affecting enrollment decisions in the digital era among new students at the University of Phayao. Descriptive statistics, including frequency, percentage, mean, and standard deviation, were utilized to analyze the factors influencing enrollment decisions, while content analysis was applied to examine students’ support needs. The results revealed that institutional factors had the greatest influence on students’ decisions to enroll at the University of Phayao in the 2025 academic year. Regarding the channels through which students became familiar with the university, personal contacts-including guidance teachers, friends or seniors, and family members-played the most significant role. Moreover, first-year students desired support in the areas of welfare and facilities provided by the university. The findings can serve as strategic guidelines for enhancing institutional public relations and educational marketing, as well as for strengthening the university’s institutional factors to better meet the needs of learners in the digital era.